A performance evaluation of silver nanorods PDMS flexible dry electrodes for electrocardiogram monitoring - C. M. Vidhya; Ghanshyam Kumar; Yogita Maithani; Bhanu Duggal; J. P. Singh (Scientific Reports)
Abstract Extensive research is being conducted in fabricating flexible dry electrodes for electrocardiogram monitoring, but the electrodes’ efficacy in clinical settings remains underexplored. In transition from research to commercial settings, investigating the electrode’s performance in real-time monitoring and patient’s comfort is very crucial. This study compares the ECG signal quality between flexible silver nanorods embedded in polydimethylsiloxane (AgNRs-PDMS) dry electrodes and commercially available metal electrodes. This study, conducted in a hospital, involves 50 subjects (40 males, 10 females; age range: 20–74) among which 41 were with cardiovascular disease and 9 normal subjects. The fabricated dry electrodes are biocompatible and have a lower skin-to-electrode impedance than the commercial electrodes, resulting in high-fidelity ECG signals. Signal quality was assessed based on parameters such as signal-to-noise ratio, mean amplitude, maximum amplitude, power spectral density, and heart rate comparison. The AgNRs-PDMS electrodes demonstrated superior SNR, confirmed using a paired t-test, with a p-value close to 0, indicating a significant difference in comparison with commercial electrodes. The amplitude of ECG signals captured by AgNRs-PDMS electrodes and the heart rate were observed to be comparable to metal electrodes. For automated arrhythmia classification of the ECG signals, two models were implemented. The first model utilized R-R interval for arrhythmic rhythm classification, while the second model used principal component analysis (PCA) for dimensionality reduction followed by support vector machine (SVM) to classify arrhythmic beats. Large arrhythmia data sets like the MIT-BIH arrhythmia database were used for training and validating the above models. Accuracy results from the MIT-BIH test data set were 97% for the R-R interval method and 93% for the SVM method. The heart beats obtained from an arrhythmic patient using commercial metal electrodes and AgNRs-PDMS electrodes were classified using the classifiers. The AgNRs-PDMS dry electrodes offer superior signal quality, ease of use due to gel-free nature, and reusability, making them a promising alternative to commercial electrodes for clinical ECG monitoring.